Development of Student Communication Culture Thorough Internalization of Character Education - Nurbaya Nurbaya; Sri Rejeki; Muhammad Nizar; Masreza Parahadi; Piscolia Dynamurti Wintoro; Harun Joko Prayitno; Eko Purnomo (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
The purpose of this research is to develop a culture of communication for students through the internalization of character education at the Sungai Buloh Guidance Studio, Kuala Lumpur, Malaysia. The method used in this study, is to use the implementation method. Inductive and objective. The purpose of being inductive here is to draw conclusions directly about the conditions that occur to students in the Sunggai Buloh Guidance Studio. The research subjects were students of the Sungai Buloh guidance center class II, III AND VI. Methods of data collection through observation, documentation, and interviews. Data analysis uses descriptive analysis. In learning at the Sungai Buloh Guidance Studio a culture of communication is developed through the introduction of symbols and symbols of the country. Students are asked to create government structures for Indonesia and Malaysia. Students are introduced to the basics of the state through discussions and portfolios. Based on these activities students recognize the differences in symbols and symbols of the state, respect the symbols and symbols of the state, understand the differences in government structures.